Behavioural changes are a major contributing factor in the reduction of sarcopenia in caloric‐restricted ageing mice. Issue 3 (27th April 2015) - van Norren, Klaske; Rusli, Fenni; van Dijk, Miriam; Lute, Carolien; Nagel, Jolanda; Dijk, Francina J.; Dwarkasing, Jvalini; Boekschoten, Mark V.; Luiking, Yvette; Witkamp, Renger F.; Müller, Michael; Steegenga, Wilma T.
Abstract: Background: In rodent models, caloric restriction (CR) with maintenance of adequate micronutrient supply has been reported to increase lifespan and to reduce age‐induced muscle loss (sarcopenia) during ageing. In the present study, we further investigated effects of CR on the onset and severity of sarcopenia in ageing male C57BL/6 J mice. The aim of this study was to investigate whether CR induces changes in behaviour of the animals that could contribute to the pronounced health‐promoting effects of CR in rodents. In addition, we aimed to investigate in more detail the effects of CR on the onset and severity of sarcopenia. Methods: The mice received either an ad libitum diet (control) or a diet matching 70 E% of the control diet (C). Daily activity, body composition (dual energy X‐ray absorptiometry), grip strength, insulin sensitivity, and general agility and balance were determined at different ages. Mice were killed at 4, 12, 24, and 28 months. Skeletal muscles of the hind limb were dissected, and the muscle extensor digitorum longus muscle was used for force‐frequency measurements. The musculus tibialis was used for real‐time quantitative PCR analysis. Results: From the age of 12 months, CR animals were nearly half the weight of the control animals, which was mainly related to a lower fat mass. In the control group, the hind limb muscles showed a decline in mass at 24 or 28 months of age, which was not present in the CR group. Moreover, insulin sensitivity (oral glucose tolerance test) was higher in this group and the in vivo and ex vivo grip strength did not differ between the two groups. In the hours before food was provided, CR animals were far more active than control animals, while total daily activity was not increased. Moreover, agility test indicated that CR animals were better climbers and showed more climbing behaviours. Conclusions: Our study confirms earlier findings that in CR animals less sarcopenia is present. The mice on the CR diet, however, showed specific behavioural changes characterized by higher bursts of activity within a short time frame before consumption of a 70 E% daily meal. We hypothesize that the positive effects of CR on muscle maintenance in rodents are not merely a direct consequence of a lower energy intake but also related to a more active behaviour in a specific time frame. The burst of activity just before immediate start of eating, might lead to a highly effective use of the restricted protein sources available.